Education and Unemployment in Israel, 1976-1994: Reducing the Anomaly - Weisberg, Jacob; Meltz, Noah (Relations industrielles / Industrial Relations, 1999)
In industrialized economics, unemployment rates are inversely related to education levels. Data from 1963 to 1994 show that Israël is an anomaly exhibiting an inverted U-shaped relationship. Workers with 9-12 years of schooling consistently experienced a higher level of unemployment than the schooling groups with less and more education. Multivariate regression analysis of data for Israël during the 1976-1994 period indicates that this inverted U-shaped relationship is moderating. The national unemployment rate and a time trend variable had positive and significant effects tending to strengthen the inverted U-shaped relationship. However, an increase in the unemployment rate within the 0-8 education group relative to the 9-12 group and a decline in the labour force participation rate of the 0-8 group overrode these factors, resulting in a flattening of the inverse relationship. The major factor responsible for the anomaly in the education-unemployment relationship in Israël appears to be government policies intended to protect low-educated immigrants with large familles. A reduction in government support over recent years seems to have increased the exposure of the least educated to labour market forces.